A daylight-oriented multi-objective optimisation of complex fenestration systems. (15th June 2021) - Mashaly, Islam A.; Garcia-Hansen, Veronica; Cholette, Michael E.; Isoardi, Gillian
Abstract: Complex fenestration systems (CFS) are effective daylighting strategies that improve daylight performance in indoor living spaces. Nevertheless, the design of CFS is complex as it requires specialised knowledge in optical physics and advanced building simulation. This paper presents an evaluation method (CFStrace) to optimise the CFS design in a multi-objective optimisation setting. The method takes into account both architectural and environmental conditions that maximise the effect of light redirection for complex fenestration systems to its full potential. The research aims to demonstrate a multi-objective and multi-scenario optimisation methodology for designing complex fenestration systems. The parameters of the optimisation problem can be easily changed due to the parametric nature of the modelling environment used. Thus, this gives designers the flexibility to adjust the CFS parameters and decrease their discretisation. To support the presented methodology, a case study is presented to demonstrate the design process and guide designers in selecting the best design option. The case study involves the design optimisation of a sinewave-shaped light redirecting panel by tweaking its geometrical parameters and comparing the optimised result with existing light redirecting panels. The case study results indicate that optimising a CFS according to the architectural design can improve daylight metrics (such as improving the useful daylight illuminance (UDI) by +10%). The case study reveals the importance of addressing architectural and environmental constraints when designing CFS as the optimised design can differ with changing parameters such as the room depth or panel height. Highlights: The complexity of designing CFS limits their usage. A CFS design optimisation framework is developed using a new tool CFStrace. The new framework generates designs optimised for specific spaces and conditions. The framework generates optimised designs in less time compared to other workflows.